The Shade of the Saguaro / La sombra del saguaro Essays on the Literary Cultures of the American Southwest / Ensayos sobre las culturas literarias del suroeste norteamericano - Prampolini, Gaetano; Pinazzi, Annamaria (Biblioteca di Studi di Filologia Moderna, 2013)
This volume springs from that fruitful project of scientific cooperation between the humanities departments of Università di Firenze and University of Arizona which was the Forum for the Study of the Literary Cultures of the Southwest (2000-2007). Tri-cultural, at least (Native, Hispanic and Anglo-American), and multi-lingual, today's Southwest presents a complex coexistence of different cultures, the equal of which would be hard to find elsewhere in the United States. Of this virtually inexhaustible object of study, the essays here collected tackle an ample range of themes. While the majority of them are concerned with the literatures of the Southwest, still a good third falls into the fields of history, art history, ethnography, sociology or cultural studies. They are partitioned in four sections, the first three reflecting the chronology of the stratification of the three major cultures and the fourth highlighting one of the most sensitive topics in and about contemporary Southwest - the borderlands/la frontera.